"BARREN DESARTS OF ARBITRARY WORDS": LANGUAGE AND COMMUNICATION IN COLLIER AND FIELDING'S THE CRY. Issue 1 (2nd January 2016) - Barr, Rebecca Anne
ABSTRACT: This essay examines the problems of language and communication in Jane Collier and Sarah Fielding's experimental The Cry: A New Dramatic Fable (1754). Throughout Collier and Fielding's work the efficacy of language as a communicative tool is interrogated, as their protagonists pursue clarity of understanding against a backdrop of hostile misinterpretation and imperceptive abuse of words. The Cry 's hybrid of social commentary and narrative anatomizes instances of semantic and conceptual confusion, exemplifying the ways in which "arbitrary words", "perverse interpretations" and lack of linguistic care are not merely individual failings, but offences against the community. The author argues that this collaborative work participates in contemporary debates about language and the possibilities of mutual intelligibility in the wake of John Locke's An Essay Concerning Human Understanding (1690). Reading The Cry alongside James Harris's Hermes: or, A Philosophical Inquiry Concerning Language and Universal Grammar (1751), the author shows how both works celebrate the power of abstraction and the idealizing abilities of the mind against what they perceive as the reductive materialism of Locke. The Cry concludes with a peculiarly unsatisfying instance of intersubjectivity. This essay argues that The Cry 's ostensibly utopian conclusion is profoundly compromised by its authors' scepticism about communication between the sexes. Reading The Cry in light of its inquiry into language enables a re-evaluation of its failed romance narrative and helps account for the deliberately unsatisfying terms of its ending.